2021
DOI: 10.22376/ijpbs/lpr.2021.11.2.l227-235
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Endophytes as Growth Promoters and Inducers of Resistance in Tomato (Lycopersicon esculentum Mill.) against Alternaria solani

Abstract: Bio control strategies are gaining importance presently due to adverse effects caused by chemical pesticides on the environment. During our study, a total of 78 fungal endophytes were isolated from five medicinally important plants and evaluated for their efficacy in inducing resistance against the early blight pathogen caused by Alternaria solani. Among the isolates evaluated, only five endophytes were able to antagonize A. solani with a maximum inhibition of 58.53% offered by ENSM-08. All the antagonistic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Fungal endophytes Target pathogens References and different concentrations of crude oligosaccharide (CO) of EF; as a result, the vegetative and reproductive parameters of tomato were enhanced (Sujatha et al, 2021). Several research findings have reported that EFs can induce resistance in various crops against insects (Kiarie et al, 2020), nematodes (Swarnakumari and Kalaiarasan, 2017), phytopathogens (Muvea et al, 2015;Galletti et al, 2020;Urooj et al, 2021), and abiotic stresses (Lata et al, 2018;Morsy et al, 2020;Singh et al, 2021).…”
Section: Cropmentioning
confidence: 99%
“…Fungal endophytes Target pathogens References and different concentrations of crude oligosaccharide (CO) of EF; as a result, the vegetative and reproductive parameters of tomato were enhanced (Sujatha et al, 2021). Several research findings have reported that EFs can induce resistance in various crops against insects (Kiarie et al, 2020), nematodes (Swarnakumari and Kalaiarasan, 2017), phytopathogens (Muvea et al, 2015;Galletti et al, 2020;Urooj et al, 2021), and abiotic stresses (Lata et al, 2018;Morsy et al, 2020;Singh et al, 2021).…”
Section: Cropmentioning
confidence: 99%
“…Fungal endophytes, residing within plant tissues without causing apparent harm to the host [11], play a crucial role in enhancing plant tolerance to biotic and abiotic stresses, including pathogen defense [12][13][14]. For instance, Amruthesh et al [15] demonstrated that fungal endophytic seed treatment induced disease resistance against early blight in tomatoes. Similarly, Constantin et al [16] found that endophyte-mediated resistance (EMR) against Fusarium wilt disease in tomatoes was independent of certain defense signaling pathways, indicating the potential of endophytic fungi in enhancing plant resistance.…”
Section: Introductionmentioning
confidence: 99%